Se connecter à la wilderness au Parc national Banff. Un bien-être touristique caractérisé par « la déconnexion » du quotidien et « la connexion » à la nature - Morgane Müller-Roux (Revue de Géographie Alpine)
This paper strives to demonstrate the strong link between current discourses on nature and the tourist imaginaries of nature practices. Indeed, there is a dominant common discourse on nature which affirms that being in nature and its practice would be beneficial for the body and the mind. Currently, national parks seem to offer the ideal space for people to “get away from it all”, because nature - and the wilderness more particularly - is becoming more and more important within tourist imaginaries as it symbolize a break with the stress of everyday life. This study, carried out in Banff National Park, in Canada, tries in particular to illustrate these new ways of dealing with nature. These tourist practices are not without effects on the environment: as we will see through field observations that these protected territories are quickly taken over and are now overwhelmed by their success. The mountain regions and certain natural areas then suddenly undergo strong anthropogenic pressures, leaving certain managers “stunned” by this influx of visitors in search of connections with nature.